DEFINING THE CONCEPT AND TERMINOLOGY OF PHRASEOLOGY - Umarjonova Guzal Mukhtorovna (Bright Mind Publishing, 2025)
This article examines the theoretical foundations, historical development, and contemporary challenges of phraseology as an independent subfield of linguistics. The study highlights the lexical enrichment of languages, with particular attention to the emergence of new phraseological units resulting from scientific, technological, and cultural evolution. Special emphasis is placed on the diversity and inconsistency of phraseological terminology, which has long complicated the delineation of core concepts. Drawing on influential works in Russian, German, and broader European linguistic traditions, the article analyzes key definitions, classifications, and criteria proposed for identifying phraseologisms. By comparing free and fixed word combinations and exploring the semantic specificity of idioms, the research sheds light on the linguistic, stylistic, and pragmatic roles of phraseological units. The study contributes to ongoing scholarly discussions by systematizing major theoretical positions and highlighting the necessity of a unified terminological framework in modern phraseological research.
Keywords: Phraseology; phraseologism; idiom; phraseme; fixed expressions; lexical enrichment; semantic specificity; linguistic terminology; idiomaticity; German phraseology; Russian phraseology.